2016
DOI: 10.1007/s40808-016-0217-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of a suitable model for prediction of soil cation exchange capacity

Abstract: Analysis and design of land-use management scenarios requires detailed soil data. The cation exchange capacity (CEC) of soil is a basic chemical property, as it has been approved that the spatial distribution of CEC is important for decisions concerning pollution prevention, crop and farming management. Since laboratory procedures for measuring CEC are cumbersome and time-consuming, it is essential to develop an indirect approach such as pedotransfer functions to predict this parameter from more readily availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…CEC was high in tobacco-planting fields in Chenzhou, the mean value of CEC was 22.05 cmol(+) kg -1 , higher than the very high grade of CEC ( 20 cmol(+) kg -1 ). The high CEC could be attributed to the high values of fine particles, pH and OM of the samples, because many studies have proved well that CEC usually is positively correlated with clays, pH and OM, while negatively correlated with sands [5][6][7][8][9][10][11][12][13][14][46][47][48][49][50][51][52][53], and Zhang and Zhu (1993) found that the positive contribution of silts to soil CEC could not be ignored [54]. From Table 4 it could be seen that both the contents of silts and clays were high, which were ranged from 10%a56% and 10%a66% with a mean of 38% and 29%, respectively, in total constituted of 2/3 of the particle composition.…”
Section: High Cec In Tobacco-planting Fields In Chenzhoumentioning
confidence: 99%
See 2 more Smart Citations
“…CEC was high in tobacco-planting fields in Chenzhou, the mean value of CEC was 22.05 cmol(+) kg -1 , higher than the very high grade of CEC ( 20 cmol(+) kg -1 ). The high CEC could be attributed to the high values of fine particles, pH and OM of the samples, because many studies have proved well that CEC usually is positively correlated with clays, pH and OM, while negatively correlated with sands [5][6][7][8][9][10][11][12][13][14][46][47][48][49][50][51][52][53], and Zhang and Zhu (1993) found that the positive contribution of silts to soil CEC could not be ignored [54]. From Table 4 it could be seen that both the contents of silts and clays were high, which were ranged from 10%a56% and 10%a66% with a mean of 38% and 29%, respectively, in total constituted of 2/3 of the particle composition.…”
Section: High Cec In Tobacco-planting Fields In Chenzhoumentioning
confidence: 99%
“…Meanwhile, CEC is also an index for soil classification or taxonomy [3][4]. Because the traditional methods determining CEC are time-consuming and laborious, more studies were conducted to setup CEC predicting model from soil properties measured more easily [5][6][7][8][9][10][11][12][13][14], and the results showed that for different regions or soils, the variables used in predicting soil CEC are different, for examples, Rahal and Alhumairi [5] predicted soil CEC in mid-Mesopotamian plain by using texture class, bulk density, total available water content, soil color, sodium adsorption ratio, electrical conductivity and Ca2+. Khaledian et al [6] proved that soil CEC was affected by different variables in different situations, clay (positively correlated) and sand (negatively correlated) were the most influential variables for predicting CEC, CEC was significantly and negatively correlated with pH in agricultural land uses in Spain, significant positive relationship between CEC and OC in Spain, the USA, Iraq, and pasture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent researches have focused on improving the estimation accuracy of soil CEC by means of artificial intelligence (AI) techniques. Artificial neural network (ANN) model based PTF's have become popular to predict/estimate soil CEC of different soil types under diverse climatic zones (Amini et al, 2005;Bayat et al, 2014;Seyedmohammadi et al, 2016;Tang et al, 2009;Zolfaghari et al, 2016). Kalkhajeh et al, (2012) conducted the accurate prediction of soil CEC using different soft computing models.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive neuro-fuzzy inference system (ANFIS) can be an appropriate approach using the learning capability of an ANN for parameter optimization. ANFIS have been used for database management, signal processing, hydrologic applications (Jang 1993;Nayak et al 2004) and developing PTFs for estimation of paddy soils CEC (Seyedmohammadi et al 2016). Researchers have not assessed the potential of this approach in saturated soil water study.…”
Section: Introductionmentioning
confidence: 99%